The impact of music on patient tolerance during office‐based laryngeal surgery - Abdul‐Latif Hamdan; Yara Yammine; Lana Ghzayel; Jad Hosri; Zeina Maria Semaan; Marc Mourad (Laryngoscope Investigative Otolaryngology)
Abstract Objective To investigate the impact of music on patient tolerance during office‐based laryngeal surgery (OBLS). Methods All patients undergoing OBLS between February 2024 to June 2024 were invited to participate in this study. They were divided into two subgroups, those with music in the background during surgery and those without. Following surgery, all patients were asked to fill IOWA tolerance score and the VAS for discomfort ranging from 0 to 10, with 0 indicating no discomfort and 10 indicating maximum discomfort. Results A total of 87 patients undergoing 95 office‐based laryngeal surgeries (OBLS) were included, with a mean age of 54.7 years and a male‐to‐female ratio of 1.5. The most common procedure was blue laser therapy (45.3%), followed by vocal fold injection (29.5%). The mean IOWA tolerance score was 2.02. Patients who listened to music during OBLS showed a significantly higher mean IOWA tolerance score compared to those without music (2.48 vs. 1.55; p < .001). Significant differences persisted when stratified by procedure type. Additionally, the mean VAS score for discomfort was lower with music (2.27 vs. 4.21; p = .001), with a significant difference noted for laser therapy (p = .004). Conclusion The results of this investigation indicate that music has a positive effect on procedural tolerance in OBLS. Participants who underwent OBLS with music in the background had significantly higher tolerance score and less discomfort than those who had no music in the background. Music can be used as a safe nonpharmacologic modality to reduce stress and improve patient tolerance in awake OBLS. Level of Evidence 2.